The influence of mortar microstructure on its thermal expansion coefficient - Zabulionis, Darius; Marčiukaitis, Gediminas (Journal of Civil Engineering and Management, 2003)
Thermal strain is one of the factors causing additional stresses in a composite structure. It is necessary to calculate the coefficient of thermal expansion in evaluating thermal strains. According to the research, concrete is a material consisting of three phases: aggregate, interfacial transition zone (ITZ) and cement paste. The article presents the technique which enables the estimation of the thermal expansion coefficient of the mortar consisting of various aggregate fractions and covered with ITZ layer. A parametric study of various ITZ layer characteristics influencing the coefficient of thermal expansion has been carried out in the present paper. It has been determined that dry mortar or concrete could be treated as a material consisting of two components. While evaluating moist mortar or concrete it is necessary to take into account the depth of the ITZ the bulk modulus and the coefficient of thermal expansion. First Published Online: 26 Jul 2012